The Situation, Problems and Challenges of Large Power Grid Operation and Control - Jiaqing LIU; Zheng XU (发电技术, 2018)
Numerous UHVAC and UHVDC projects built and put into operation successively, has marked power grid construction in China at the international leading level. Meanwhile, the operation and control of large power grid in China is facing unprecedented problems and challenges. The article introduces the situation of large power grid, which has the characteristics of increasing proportion of new energy and long-distance transmission of power with high capacity across large areas. The problems and challenges of power grid operation and control were analyzed. Several measures were taken by Northeast China Grid, such as peak regulation ancillary service market and high frequency emergency control system, which promote coordination of grid and source and new energy integration.